Study of natural organic dyes as active material for fabrication of organic light emitting diodes. - Obregón, D. (2016)
The scientific community and some sectors of industry have been working with organic dyes for successful applications in OLEDs, OSCs, however, most of the used dyes and pigments are synthetic. In this work is investigated the use of natural dyes for its application in organic light emitting diodes, some of the studied species are chili, blackberry, guayacan flower, cochinilla, tree tomato, capuli, etc. In this study the dyes are deposited by direct deposition and SOL-GEL process doped with the natural organic dye, both methods show good performance and lower fabrication costs for dye extraction, this represents a new alternative for the fabrication of OLED devices with low requirements in technology. Most representative results are presented for Dactylopius Coccus Costa and raphanus sativus skin.